Identification of methylated transcripts using the TRIBE approach - Worpenberg, Lina; Jakobi, Tobias; Dieterich, Christoph (Epitranscriptomics, 2019)
m6A is the most abundant internal modification on mRNA. Recent improvements of high-throughput sequencing techniques enables its detection at the transcriptome level, even at the nucleotide resolution. However most current techniques require large amounts of starting material to detect the modification. Here, we describe a complementary technique of standard meRIP-seq/miCLIP-seq approaches to identify methylated RNA using a low amount of material. We believe this approach can be applied in vivo to identify methylated targets in specific tissues or subpopulations of cells.